2010
DOI: 10.1038/pcan.2010.7
|View full text |Cite
|
Sign up to set email alerts
|

Prostate biopsy in Western Australia 1998–2004

Abstract: We reviewed the status of prostate cancer diagnosis in Western Australia (WA) with the aim of improving decision-making about PSA testing and prostate biopsy. Our patient cohort was 5145 men undergoing an initial biopsy for prostate cancer diagnosis in WA between 1998 and 2004. Transrectal ultrasound-guided biopsies were performed by one of 18 clinicians whereas all pathology was assessed by one urological pathologist. Cancer detection rates were 59% for initial biopsies and 32% for repeat biopsies. High-grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We were also unable to explore the effects of increased PSA testing, which may result in increased registration of low-grade cancers that would have otherwise gone undetected. PSA testing is subsidized by the Australian public health system and (49). Thus, the threshold for biopsy seems to be high, and the spectrum of disease in our sample may be shifted upward relative to studies from other regions with a high prevalence of PSA testing.…”
Section: Discussionmentioning
confidence: 74%
“…We were also unable to explore the effects of increased PSA testing, which may result in increased registration of low-grade cancers that would have otherwise gone undetected. PSA testing is subsidized by the Australian public health system and (49). Thus, the threshold for biopsy seems to be high, and the spectrum of disease in our sample may be shifted upward relative to studies from other regions with a high prevalence of PSA testing.…”
Section: Discussionmentioning
confidence: 74%
“…In fact, contemporary series from USA institutions show a risk of LN disease generally < 5% [ 6, 7,15 ] , although the rate appears to be higher in European centres 15 ] . This difference again confi rms that the spectrum of prostate cancer treated in the Australian practice environment differs somewhat from that seen in USA centres [ 16 ] .…”
Section: Discussionmentioning
confidence: 85%
“…The present data is obviously of greatest relevance to the Australian practice context, and it is important to consider the unique features in the Australian epidemiology of prostate cancer that have been demonstrated [ 16 ] . Nonetheless, we feel that the principles of patient selection for PLND that we have developed from the present study should have wide applicability, as suggested by similar recommendations from the EAU.…”
Section: Discussionmentioning
confidence: 89%